Analysis of Factors Affecting Non-Adherence to Treatment in Type 2 Diabetes Mellitus Patients at Jatilawang Community Health Center - Irawati, Dhela Puja; Anandari, Dian; Rahardjo, Setiyowati (Universitas Nahdlatul Ulama Surabaya, 2026)
Diabetes mellitus is a chronic metabolic disorder marked by elevated blood sugar. Non-adherence to type 2 DM treatment increases risks of complications and failure of blood sugar control. This quantitative cross-sectional study used spatial and network analysis to examine factors affecting non-adherence among 114 type 2 DM patients registered as prolanis participants at the Jatilawang Community Health Center. Data collection involved questionnaires, interviews, and geospatial mapping via Google Maps. Statistical analyses included univariate, bivariate, multivariate analysis with SPSS, and network mapping with QGIS. The study found that access to health information significantly influenced non-adherence (p-value=0.006, OR=5.170), while transportation availability (p-value=0.427, OR=0.609) and family support (p-value=0.076, OR=2.622) were confounding factors. Other variables, such as knowledge, attitude, motivation, distance to the community health center, and the role of health workers, were not significant. Most respondents lived within 3 km of the community health center based on network mapping. The findings suggest that patients should actively seek health information from healthcare providers to enhance treatment adherence.